The Influence of Live-Streamers on Somethinc’s Purchase Intention at Tiktok Shop Mediated by Consumer Trust - Liizza Diana Manzil; Amelindha Vania (Jurnal Informatika Ekonomi Bisnis, 2023)
The trend that is happening nowadays is online transactions through live-streaming or what is commonly known as live-streaming shopping. This study aims to determine the effect of live-streamers on purchase intention with consumer trust as an intervening variable. This research uses descriptive quantitative method. The population in this study are state university students who use social media TikTok in Malang City. The sample in this study amounted to 195 respondents, determined using a purposive sampling technique with criteria such as students aged 18-28 years who are TikTok social media users in Malang City who have watched live-streaming on the official TikTok account of @Somethincofficial, and have ever used TikTok Shop feature. The data analysis technique used in this study is Structural Equation Modeling (SEM) Partial Least Square (PLS) or SEM-PLS with the help of SmartPLS 3.0 software. The results of this study indicate that live-streamers have a positive and significant effect on consumer trust, live-streamers have a positive and significant effect on purchase intention, consumer trust has a positive and significant effect on purchase intention, and live-streamers have a positive and significant effect on purchase intention through consumer trust.